The Role of Prices in Welfare Comparisons: Methodological Developments and a Selective Survey of the Empirical Literature1. Issue 301 (1st February 2017) - Ray, Ranjan
Abstract : Prices play a central role in a wide range of applications in economics, ranging from macro topics such as inflation targeting, purchasing power parity between currencies, global poverty and real Gross Domestic Product (GDP) comparisons to micro topics such as inequality and poverty at household level and the distributive effects of price movements. The literature on price measurement has also impacted on, and been impacted by, developments in the demographic demand literature based on the treatment of household composition as analogous to prices. While there is now a sizeable statistical literature on price measurement, there is hardly any survey of the empirical economics literature where prices play a central role in the analysis. This paper attempts to address this gap and provides a survey of the methodological developments in price measurement followed by a selected review of their empirical applications.